2015
DOI: 10.1111/are.12885
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the bioavailability of L-methionine and a methionine hydroxy analogue (MHA-Ca) compared to DL-methionine in rainbow trout (Oncorhynchus mykiss)

Abstract: Different synthetic forms of supplemental methionine (Met) are produced commercially by various manufacturers. Limited information exists on the bioavailability of these different forms in commercially relevant fish species. The objective of this study was to compare the relative bioavailability of L-methionine and a methionine hydroxy analogue calcium salt (MHA-Ca) to DL-methionine in a commercially relevant species, rainbow trout, using a linear slope-ratio assay. In addition, the ability of the rainbow trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
(78 reference statements)
8
23
0
Order By: Relevance
“…The quantity of methionine had no effect (p > 0.05) on the performance of broilers in the finisher period. This finding confirms the reports of earlier researchers [21,22] who observed that levels of methionine had no effect on feed intake, average daily gain, feed efficiency and FCR of broilers because DL-Met is readily converted into the L-isomer by the animal. Also, our finding that L-Met and DL-Met had no combined effect on feed intake, weight gain and FCR during the overall phase of broiler growth is supported by other researchers [33,35,36] who also observed that L-Met or DL-Met did not influence the feed intake, weight gain and overall FCR of broilers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The quantity of methionine had no effect (p > 0.05) on the performance of broilers in the finisher period. This finding confirms the reports of earlier researchers [21,22] who observed that levels of methionine had no effect on feed intake, average daily gain, feed efficiency and FCR of broilers because DL-Met is readily converted into the L-isomer by the animal. Also, our finding that L-Met and DL-Met had no combined effect on feed intake, weight gain and FCR during the overall phase of broiler growth is supported by other researchers [33,35,36] who also observed that L-Met or DL-Met did not influence the feed intake, weight gain and overall FCR of broilers.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the cystine deficiency results in the reduction in the recovery of breast meat and also decreases the extent of feathering. Our finding of no effects of the sources of methionine on the starter phase of broilers is supported by other researchers [22,31] who observed that L-Met and DL-Met did not affect growth performance due to conversion of DL-Met into L-Met. It seems that lower metabolization of D-amino acid due to the lower amount of D-amino acid oxidase in young broilers may reduce the utilization of higher amounts of DL-Met, which leads to metabolic stress and inhibition of body weight gain in the starter phase.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The crude protein, fat, starch, oil, acid detergent fiber, neutral detergent fiber, sugar and digestibility (NCGD) values were determined following standard laboratory procedures and energy values were calculated (Núñez-Sánchez et al, 2012;. Essential and non-essential amino acid contents of BSF larvae and experimental diets (Table 1) were analyzed by AMINOLab® (Evonik Industries, Hanau, Germany) using an amino acid analyzer (Biochrom 30 plus, Biochrom Ltd. Cambridge, UK) (Al Powell et al, 2017;. Feed samples were homogenously ground with an Ultra Centrifugal Mill RETSCH-ZM 200 to pass through a 0.5 mm sieve.…”
Section: Proximate Amino Acids and Mineral Composition Of Experimentmentioning
confidence: 99%